Accurate and convergent T-matrix calculations of light scattering by spheroids. (July 2015) - Somerville, W.R.C.; Auguié, B.; Le Ru, E.C.
Abstract: The convergence behavior of the T -matrix method as calculated by the extended boundary condition method (EBCM) is studied, in the case of light scattering by spheroidal particles. By making use of a new formulation of the EBCM integrals specifically designed to avoid numerical cancellations, we are able to obtain accurate matrices up to high multipole order, and study the effect of changing this order on both the individual matrix elements and derived physical observables. Convergence of near- and far-field scattering properties with a relative error of 10 −15 is demonstrated over a large parameter space in terms of size, aspect ratio, and particle refractive index. This study demonstrates the capability of the T -matrix/EBCM method for fast, efficient, and numerically stable electromagnetic calculations on spheroidal particles with an accuracy comparable to Mie theory. Abstract : Highlights: We study the convergence of the T-matrix method for EM scattering by spheroids. The chosen double-precision implementation is fast and free from numerical issues. Convergence to better than 10 −12 relative accuracy is obtained. Convergence is demonstrated for difficult cases (aspect ratio up to 100).